Interactional dominance in legal discussions on YouTube: A conversation analysis of the Vina murder case - Martin, Martin; Suratno, Antonius (LingTera, 2025)
This study investigates the strategies employed by participants to assert dominance in a legal discussion featured in the YouTube video “Janggalnya Kasus Vina Menyasar ke Mana-mana.” Adopting an ethnomethodological approach grounded in Conversation Analysis (CA), the study identifies key dominance strategies, including turn-taking control, interruptions, overlaps, topic shifting, and assertive language use. These strategies serve as critical tools for establishing dominance in high-stakes interactions such as legal debates. The analysis utilized the Jefferson Transcription System to examine how conversational control influences the progression and outcomes of legal discussions. Findings indicate that legal practitioners with institutional authority, expertise, or professional standing assert dominance through assertive language, strategic questioning, and frequent interruptions, while other participants assume less dominant roles. The study contributes to understanding how interactional dominance operates in formal legal settings, where institutional status and expertise often outweigh previously emphasized factors such as gender. These insights have practical implications for legal and communication professionals navigating power dynamics in formal discourse.